The use of armed drones for counter-terrorism purposes: whether customary international law? - Kleinberga, Anete (Riga Graduate School of Law, 2019)
The vast and rapid development of technologies constantly creates gaps in the law within both the international and national law systems. One of such technologies the increased usage of which for military purposes has instituted a debate on the applicable law for its use under the existing legal frameworks is the technology of armed drones, also known as armed unmanned aerial vehicles (AUAVs). The source of the debate is the presumption that armed drones are almost exclusively used for counter-terrorism purposes, thus involving their use against non-state actors operating in a country that a state is not in war with. The author of this thesis will, first of all, identify the established legal framework regulating the use of armed drones in order to identify the gaps in the existing law. Following that the author will further focus the research on the possible emergence of customary international law on the use of armed drones for counter-terrorism purposes. In order to reach the final conclusion about their legality, with a focus on the possibility to determine the emergence of customary international law, the author will aim at determining existing practices and opinio juris regarding their use.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Customary international law; Armed conflicts; Drones